1974
DOI: 10.2514/3.59257
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hypermixing for Thrust Augmenting Ejectors

Abstract: Steady-state distortion levels produced during full scale P 3 G operation as evaluated in terms of IDC (circumferential) and IDR (radial) distortion parameters were generally less 0.02 and nominally 0.01 or less as previously realized in the model test. Figure 10 summarizes the circumferential planarity in terms of phase and amplitude. The probe readings from two of the rakes, 180° apart, at the engine IGV plane were averaged to obtain these summary results. Such a comparison indicates excellent circumferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 4 publications
(3 reference statements)
0
17
0
Order By: Relevance
“…The definition used here is similar to that used by Bevilaqua (1978) to evaluate the thrust distribution. Ideally, at the location where the two streams at the wake region with different velocities were to be completely mixed, and spatial uniformity was achieved, the momentum distribution would be uniform and the shape factor should be equal to unity.…”
Section: Shape Factormentioning
confidence: 99%
See 1 more Smart Citation
“…The definition used here is similar to that used by Bevilaqua (1978) to evaluate the thrust distribution. Ideally, at the location where the two streams at the wake region with different velocities were to be completely mixed, and spatial uniformity was achieved, the momentum distribution would be uniform and the shape factor should be equal to unity.…”
Section: Shape Factormentioning
confidence: 99%
“…Bevilaqua (1978), Povinelli et al (1980) and Paterson (1982) found that there were strong streamwise vortices generated in the wake of lobe-forced mixers. Experimental investigations by Skebe et al (1988) and Barber et al (1988), and the computational studies by O'Sullivan et al (1996) found that both the lobe shape and its penetration angle were important parameters in determining the effectiveness of mixers.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…With this in mind, attempts have been made by several investigators to improve the mixing through various types of nozzle designs, for example, the hyper mixing nozzle. 6 Although the ejector has been the subject of many research investigations, experimental results for ejectors operating at practical engine pressures and temperatures are scarce. It is known that when the stagnation pressure of a jet issuing from a convergent nozzle exceeds the critical pressure, the jet becomes underexpanded and exhibits quite different behavior from that of a subsonic jet.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the code can solve grids that are made up of multiple grid blocks. Grid blocking allows one (1) to break up a complex domain into smaller sections, which separately use less computer memory than a single large grid and (2) to break up complex shapes into simpler components, which simplifies grid generation. Two grids that comprise a block interface do not have to be contiguous, which allows grid points across a block boundary to be reduced.…”
Section: Discussionmentioning
confidence: 99%